Manajemen Pemanfaatan Dana Desa Dalam Pembangunan Infastruktur Di Desa Puse Kecamatan Dampal Selatan Kabupaten Toli-Toli - Daniel T. Todapa; Juemi Juemi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Management of Village Fund Utilization in Infrastructure Development carried out by the Village Government to support community development and empowerment. Qualitative research method with a descriptive approach by examining four aspects, namely planning, organizing, mobilizing and supervising. Data collection techniques include observation, interviews, documentation and triangulation. The determination of informants was carried out